Viewpoint: Characterising early agricultural and food policy responses to the outbreak of COVID-19. (April 2021) - Gruère, Guillaume; Brooks, Jonathan
Highlights: Diverse early food policy measures were adopted in response to COVID-19. OECD countries used more economic support, emerging economies more market and trade measures. About a third of 496 reported measures were urgent and necessary or "no-regret" 10.5% of measures had potentially negative impacts on markets, trade or the environment. At least $47.6 billion was allocated by OECD governments to the food sector. Abstract: This article reviews and categorises early policy responses to the COVID-19 pandemic, based on a dataset of 496 measures taken by 54 countries between January 1 and April 28 and collected by the OECD from government officials and additional sources. Findings show a large diversity of measures, some of which were urgent and necessary, some that may continue to be beneficial once the pandemic has subsided, while others are potentially disruptive for the functioning of markets or damaging for the environment. National allocations of measures show differences between developed OECD countries, which used more agriculture or support related measures, and emerging economies, which focused on trade policies, information provision or food assistance. A minimum USD 47.6 billion was allocated by OECD governments to the agriculture and food sector, mostly in the form of domestic food assistance and support to agriculture and the food chain.